THE EFFECT ANALYSIS OF MARKETING MIX ON PURCHASE DECISIONS AND CUSTOMER LOYALTY USING STRUCTURAL EQUATION MODELING METHOD - Suparto, Suparto (Tibuana, 2020)
Distros have been known by the general publicespecially millennial who are fond of the brandor brand image of a product. The number ofvery tight competition makes Lollypop ShopSurabaya as one of the distributions that are inneed of designing the right marketing strategy.The purpose of this study was to determine theeffect of 4P marketing mix variables consistingof products, price, place and promotion ofpurchasing decisions and customer loyalty asa consideration of business owners indetermining marketing strategies. Dataanalysis was performed using the StructuralEquation Modeling (SEM) method whichinvolved 120 respondents obtained from thepurposive sampling method. The results of theanalysis show that product and promotionvariables have a positive and significant effecton purchasing decisions. Price and placevariables have a positive but not significanteffect on product purchasing decisions.Product variable is the variable that mostinfluences the purchasing decision of LollypopShop Surabaya products with product variantsas the indicators most desired by consumers.